Associations between peak expiratory flow and frailty in olderly individuals: findings from the China health and retirement longitudinal study - Wang, Rui; Shi, Wen; Zhou, Wenlu; Xu, Yawen; Wang, Junjie (Frontiers in Public Health, 2024)
Purpose: Peak Expiratory Flow (PEF) is associated with a variety of adverse health outcomes in older adults; however, the relationship between PEF and frailty remains uncertain, and this study investigated the relationship between PEF and frailty within an olderly Asian demographic. Methods: Data were sourced from the Chinese Health and Retirement Longitudinal Study (CHARLS). Individuals in the study, all 60 years or older, underwent baseline PEF assessments quantified as standardized residual (SR) percentile values. The evaluation of frailty was conducted based on the criteria established by Fried. Participants without frailty at the outset were tracked over a four-year period, during which the relationships between PEF and frailty were examined through logistic regression and discrete-time Cox regression analyses.Results: Among 5060 participants, cross-sectional analysis revealed that the prevalence of frailty was 2-3 times higher in the lower 10-49th and <10th SR percentile groups compared to the 80-100th SR percentile group. The longitudinal study corroborated these results, showing an adjusted hazard ratio (HR) of 2.01 (95% CI: 1.15-3.51) for PEF SR percentiles below the 10th, in contrast to those between the 80th and 100th percentiles.Conclusion: PEF independently predicts and determines frailty in older adults. Declines in PEF greater than expected are associated with the development of frailty. Subsequent studies are encouraged to delve deeper into the connection between respiratory function and frailty in diverse contexts.